FROM FIG TO SLANG: A SEMANTIC-PRAGMATIC INVESTIGATION OF 'ANJIR' IN CONTEMPORARY INDONESIAN DISCOURSE - Rahmat, Subhan (Universitas Muhammadiyah Lampung, 2025)
This study examines the phenomenon of using the word anjir as a popular emotional expression in informal conversations within modern Indonesian society. This phenomenon reflects the dynamic nature of language and cultural familiarity in everyday communication. Through a semantic and pragmatic approach, this research aims to analyze the function of anjir in various social and situational contexts. Data were collected using questionnaires distributed to respondents and analyzed using a mixed-method approach, combining qualitative methods to understand social contexts and quantitative methods to measure the frequency and patterns of usage. The results show that anjir is most frequently used to express surprise (58.8%), followed by humor (29.4%), admiration (14.1%), and anger (1.1%). These findings reveal that anjir functions as an emotional amplifier and a tool for fostering closeness in informal conversations, although its usage is considered less appropriate in formal situations. This study highlights the flexibility of linguistic expressions in adapting to modern communication needs while contributing to the semantic and pragmatic studies of the Indonesian language.